An investigation into the relationship between synthetic aperture radar (SAR) data and beach sediment grain size - Mann, Sophie (2022)
Sediment grain size on beaches has been established as a crucial parameter to determine shoreline changes and provide coastal protection. However, traditional surveying techniques are time-consuming, with records becoming outdated quickly. The use of Synthetic Aperture Radar (SAR) data for this application will enable quick surveying of beaches and is particularly useful due to the ability to collect data irrespective of weather-conditions. This study aims to evaluate if there is a relationship between sediment grain size on beaches and the backscatter from satellite SAR data. As part of this investigation, a fieldwork methodology has been constructed and carried out to obtain ground-truth data for beach sediment grain size and elevation. Results show a strong positive correlation between backscatter from C-band Sentinel-1 data and median sediment grain size on beaches. However, only a moderate correlation was found between backscatter from S-band NovaSAR data and median sediment grain size. These results are mainly attributed to the size of the sediment analysed in this study, compared to the SAR wavelength, along with increasing surface roughness as sediment size increases.